Fire in the Wildland-Urban Interface: Reducing Wildfire Risk While Achieving Other Landscaping Goals - Cotton K. Randall; L. Annie Hermansen-Báez; Glenn Acomb (EDIS)
Circular 1478, an 8-page illustrated publication by Cotton K. Randall, L. Annie Hermansen-Báez, and Glenn Acomb, gives a brief overview of several different landscaping goals, including wildfire risk reduction (Firewise), wildlife habitat creation or enhancement, water conservation, and energy conservation. It introduces the main principles and compares each to firewise landscaping. It also briefly discusses examples of programs and guidelines that incorporate multiple goals. Includes additional resources and a table showing compatibilities of several landscaping goals and firewise landscaping principles. Published by the UF School of Forest Resources and Conservation, October 2006.